Tailoring mediation to learners' ZPD: effects of dynamic and non-dynamic corrective feedback on L2 development. Issue 5 (20th October 2019) - Rassaei, Ehsan
ABSTRACT: The current study investigates the effects of dynamic and non-dynamic oral corrective feedback in response to learners' errors on English as a foreign language (EFL) learners' English wh -question development over three treatment sessions. Sixty-eight EFL learners were assigned randomly to one of two experimental conditions that received either dynamic or non-dynamic feedback and a control condition. Dynamic feedback was operationalised in the context of dyadic interaction as a feedback sequence that targeted learners' zone of proximal development (ZPD) by providing dynamic prompts that were initially in the form of implicit hints and became increasingly more explicit until the learner received sufficient help to revise his or her incorrect form. The non-dynamic feedback included several fixed corrective feedback moves with no concern for learners' ZPD. Learners' scores obtained from two testing instruments, a picture description task and a question generating task, indicated that compared to the control group, both experimental conditions had statistically significant effects on the development of target form. Meanwhile, the findings suggested that the dynamic feedback condition had more profound effects on L2 development than did the non-dynamic feedback condition. Qualitative examination of the dynamic group's interactions in the three treatment sessions also provided further insight into how dynamic feedback assists L2 development.